(untitled) (Conferencea, 2023)
For the full growth and development of a child, not only proteins, fats and carbohydrates are needed, but also vitamins, macro-and microelements in quantities corresponding to physiological needs. The lack of any of these substances negatively affects the health, growth and development of the child. An increase in the norm and a change in body weight in preschool and primary school age is very noticeable: if at the age of 1.5 the child’s body weight is 11-12 kg, then at 6.5 years old he doubles and weighs 20-24 kg. Permanent tooth changes in milk teeth occur at the age of 5-6 years. High skeletal growth rate and the formation of bone tissue, increased metabolic processes require constant intake of protein, vitamin D and calcium in sufficient quantities with food. The purpose of our work is to analyze the vitamin and mineral elements in the diet of children’s real food, in which there are complications after rickets. Our scientific research was conducted among 30 children (12 boys and 18 girls) with complications after rickets living in Nukus, Karakalpakstan Republic.